EFFECTIVENESS OF CASE REGISTRATION SERVICES VIA THE E-COURT APPLICATION IN RESOLVING CASES AT THE CIBINONG RELIGIOUS COURT - Pracipta, Dwi Wahyu Nur; Yono, Yono; Nawawi, Kholil (JURNAL ILMU SYARIAH, 2024)
Electronic Court is an innovative application of the Supreme Court as a form of service to the community with the aim of implementing justice principles that are simple, fast, and low cost. The aim of this research is to determine the effectiveness of case registration services through the e-court application in resolving cases at the Cibinong Religious Court. The research method used in this writing is qualitative research using empirical juridical methods. Supreme Court Regulation Number 7 of 2022 is the latest regulation which is the basis for the application of e-court to the wider community. The results of this research show that the registration service via e-Court at the Cibinong Religious Court is running effectively as seen by the development of Supreme Court Regulations and the increase in case registration via e-Court for registered users and incidental users by 676 cases or an increase of 28% between 2021 and 2022. Dissemination of information regarding e-court must be intensively carried out to the public so that parties seeking justice can resolve cases simply, quickly, and at low cost.